2016
DOI: 10.1098/rspb.2016.1585
|View full text |Cite
|
Sign up to set email alerts
|

Why many Batesian mimics are inaccurate: evidence from hoverfly colour patterns

Abstract: Mimicry is considered a classic example of the elaborate adaptations that natural selection can produce, yet often similarity between Batesian (harmless) mimics and their unpalatable models is far from perfect. Variation in mimetic accuracy is a puzzle, as natural selection should favour mimics that are hardest to distinguish from their models. Numerous hypotheses exist to explain the persistence of inaccurate mimics, but most have rarely or never been tested against empirical observations from wild population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…In all our analyses, wing length was a good predictor of wasp mimicry (Tables 1 and 2). Larger species were typically better wasp mimics, which corresponds with experimental results and theoretical hypotheses from previous papers (Penney et al 2012;Taylor et al 2016a). There may be greater selection pressure on larger hoverflies to deceive predator visual systems because they are more nutritionally profitable prey items (Penney et al 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In all our analyses, wing length was a good predictor of wasp mimicry (Tables 1 and 2). Larger species were typically better wasp mimics, which corresponds with experimental results and theoretical hypotheses from previous papers (Penney et al 2012;Taylor et al 2016a). There may be greater selection pressure on larger hoverflies to deceive predator visual systems because they are more nutritionally profitable prey items (Penney et al 2012).…”
Section: Discussionsupporting
confidence: 88%
“…The abdomen was used for analysis because the color pattern is, in general, much more distinctive and variable on the abdomen than on the thorax in dipterans and hymenopterans (Marchini et al 2017), and the abdomen is typically conspicuous to potential predators. Studies have previously shown that abdominal color patterns of both hoverflies and wasps consist of clearly delineated contrasts in both achromatic and chromatic dimensions, and do not contain hidden ultraviolet signals (Taylor et al 2016b), meaning that the spatial elements of the pattern are visible to all but the most primitive of visual systems.…”
Section: Image Selectionmentioning
confidence: 99%
“…Alternatively, C. coccinea might fail to show mimicry on the edge if there is a selective trade‐off between mimicry and thermoregulation: mimics that occur at higher latitudes might need more black coloration to achieve optimal body temperatures more rapidly (as in hoverflies; see Taylor et al ., ). Contrary to this expectation, however, all snake species – both mimics and models – either had less black on their patterns at higher latitudes or did not vary significantly with latitude (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…How general our results will prove to be beyond coral snake mimics is uncertain. Most studies of variation in mimetic precision in insects have examined variation between species (Penney et al, 2012;Taylor et al, 2013;Wilson et al, 2013;Taylor et al 2016b). The few studies that have examined variation in mimetic precision within species in insects (Iserbyt et al, 2011) and other vertebrates (Kraemer et al, 2015) did not examine multiple mimic species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Darst & Cummings [14] found that a poison frog mimic that co-occurs with two poison frog models only resembled a single model well. Similarly, Penney et al [64] and Taylor et al [65] failed to find any evidence that hoverfly mimics were intermediate in phenotype between different model wasp and bee species.…”
Section: Discussionmentioning
confidence: 98%